PerCEN trial participant perspectives on the implementation and outcomes of person-centered dementia care and environments. (26th August 2015) - Chenoweth, Lynn; Jeon, Yun-Hee; Stein-Parbury, Jane; Forbes, Ian; Fleming, Richard; Cook, Janet; Cheah, Seong; Fletcher, Stephanie; Tinslay, Leonie
ABSTRACT: Background: Well-being and various forms of agitation in people with dementia can be improved in a person-centered long-term care setting. Data obtained during the Person-Centered Dementia Care and Environment (PerCEN) randomized controlled trial shed light on the factors that influenced the adoption and outcomes of person-centered interventions in long-term care from the perspective of study participants. Methods: Data were obtained from PerCEN participants: individual semi-structured interviews with care managers (29), nurses and care staff (70); telephone surveys with family members (73); staff reports of care approaches; and 131 field note entries recorded by the person-centered care and environment facilitators. Data were interpreted inductively using content analysis, code building, theme development, and synthesis of findings. Results: All data sources confirmed that, when adopted, the person-centered model increased the number and variety of opportunities for resident interaction, improved flexibility in care regimens, enhanced staff's attention to resident needs, reduced resident agitation, and improved their well-being. Barriers and enablers for the person-centered model related to leadership, manager, staff and family appreciation of the model, staff's capacity, effective communication and team work among direct care staff, care service flexibility, and staff education on how to focus care on the person's well-being. Conclusions: Successful knowledge translation of the person-centered model starts with managerial leadership and support; it is sustained when staff are educated and assisted to apply the model, and, along with families, come to appreciate the benefits of flexible care services and teamwork in achieving resident well-being. The Australian New Zealand Clinical Trials Registry number is ACTRN 12608000095369.